Potential Opportunities for the Growth of the Russian Economy and the Monetary Policy of the Bank of Russia - Glazyev Sergey Y. (Economic and Social Changes: Facts, Trends, Forecast, 2018)
The paper considers the role and place of monetary policy in ensuring the reproduction of modern economy. Monetary policy conducted by the Bank of Russia is based on the IMF’s universal recommendations, which are inconsistent both with the conditions of reproduction of the Russian economy and with specific features of the current period of structural changes in the world economy. The ongoing change of technological and world economic orders is accompanied by fundamental changes in the composition of the industries that determine economic growth, as well as in the system of institutions for managing economic reproduction. The resulting opportunities for a breakthrough in the development of the Russian economy can be implemented only in conditions of an appropriate monetary policy focused on lending to promising areas of economic growth within the existing production factors. The goal of the present paper is to substantiate the mismatch between the monetary policy and the potential opportunities for the growth of the Russian economy in the conditions of changing technological and global economic orders. The paper criticizes the draft major directions of the unified state monetary policy for 2019 and for the period of 2020–2021 and proves that they are inconsistent with modern knowledge about the laws of economic development and growth opportunities of the Russian economy